E-learning critical success factors and motivation to learn: a study in Universiti Teknologi MARA Kelantan / Syamimi Zakaria - Zakaria, Syamimi (2014)
This study investigated the critical success factors of e-learning toward motivation to learn among Information System Management undergraduate students in UiTM Kelantan. In particular, the study explored the various critical success factors that could influence students' motivation to learn using i-Learn Portal. Based on the findings obtained in this study through the application of a systematic research methodology, the research model that was the theoretical framework which represented the six critical success determinant factors of eLearning have influenced the motivation to learn among undergraduate and their interrelationships formulated. Using stratified random sampling, the primary data was collected through self-administered questionnaires among respondents who studied in different semesters varying in different group of classes. Study findings have revealed that there was a significant relationship between e-learning critical success factors and motivation to learn among them. Service quality was found to be the highest significant correlated with motivation to learn while learner's characteristics was found to be the lowest significant correlated with motivation to learn. Moreover, system quality was identified as the most preferred determinant to motivate the students to use e-leaming. As only one program was directly involved in the study, it was expected that future research could enhance the samples to different degree programs so that the findings might be generalized and more unexpected findings would be discovered. It was also recommended that information literacy module would be embedded into existing i-Leam training to enrich undergraduate information management skills to produce more independent and lifelong learners for future workforce.